Factors Influencing Students Intention To Spend Under Goods And Services Tax Regime - Mahmood, Ahmed Obaid (2018)
The main way to collect the government revenue from individuals, companies and the other entities is by using tax. There are several types of taxes that the people have to pay, one of those is goods and services tax (GST) which consider as broad-based that cover almost all the transactions including the goods and services that imported, except the one that assorted as zero supply and exempt supply thus it will be exempt by the government. This study aims to investigate how this tax will affect the student spending behavior by using the theory of planned behavior (TPB) by determining the level of each of the factors which are attitudes, subjective norms, GST knowledge, government subsidies and the intention to spend among postgraduate student in Universiti Utara Malaysia (UUM). Also, by determining the relationship between attitudes, subjective norms, GST knowledge, government subsidies and the intention to spend among postgraduate student in UUM. Furthermore, this study attempts to provide some insight into the government in order to rise the student spending. This study done based on 360 questionnaires that have been responded by the postgraduate students of UUM. In this study five metrics of variables have been used, one dependent (student intention to spend) and four independents (attitude, subjective norms, GST knowledge and government subsidy). Descriptive and inference analysis were used for this study to describe the variables and to test the hypotheses. All variables are significantly affecting the intention to spend under GST among postgraduate students.